SEJARAH DAN PERKEMBANGAN DINAS ARSIP DAN PERPUSTAKAAN PEMATANG SIANTAR: MENUJU MASYARAKAT YANG LEBIH CERDAS DAN BERLITERASI - Ade Karya Siburian; Nopi Rifka Laia; Vanesia Amelia Sebayang; Lestari Dara Cinta Utami Ginting (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
Libraries as centers of information and culture have an important role in the development of urban society. This research reviews the transformation of the Pematang Siantar Archives and Library Service from a public library to a government agency that manages archives and libraries. Historical research methods were used to research the 2017-2023 period, including heuristics, source criticism, interpretation, and historiography. Despite facing challenges, the agency is trying to maintain its vision and mission in improving literacy and public education, especially during the COVID-19 pandemic. Improved services and facilities, such as the Audio Visual room, have increased public interest. However, additional book collections are still needed. In conclusion, the Pematang Siantar Archives and Library Office plays a crucial role in educating the community. Efforts continue to be made to improve the quality of services, in accordance with the vision and mission to provide maximum benefits for the people of Pematang Siantar City